Is sugar as sweet to the palate as seeds are appetizing to the belly? Taste responsiveness to five food-associated carbohydrates in zoo-housed white-faced sakis, Pithecia pithecia. - Mikel Redin Hurtado; Ida Fischer; Matthias Laska (PLoS ONE, 2023)
Differences in taste perception between species are thought to reflect evolutionary adaptations to dietary specialization. White-faced sakis (Pithecia pithecia) are commonly considered as frugivores but are unusual among primates as they do not serve as seed dispersers but rather prey upon the seeds of the fruits they consume and are thought to exploit the lipids and proteins that these seeds contain in high amounts. Using a two-bottle preference test of short duration we therefore assessed whether this dietary specialization affects the taste responsiveness of four adult white-faced sakis for five food-associated carbohydrates. We found that the sakis significantly preferred concentrations as low as 10 mM sucrose, 10-40 mM fructose, 20-30 mM glucose and maltose, and 30-40 mM lactose over tap water. When given the choice between all binary combinations of these five saccharides presented at equimolar concentrations of 100, 200, and 300 mM, respectively, the sakis displayed significant preferences for individual saccharides in the following order: sucrose > fructose > glucose ≥ maltose = lactose. These results demonstrate that seed-predating white-faced sakis have a well-developed taste sensitivity for food-associated carbohydrates which is not inferior to that of most other primates including seed-dispersing frugivores, but rather ranks among the more sweet-taste sensitive species. Further, they show that their pattern of relative preference for the five carbohydrates is similar to that found in other frugivorous primate species. These findings may represent an example of Liem's paradox as the sakis' morphological adaptations to efficiently predate on and exploit the lipid- and protein-rich hard-shelled seeds of fruits does not compromise their ability to detect the carbohydrates found in the pulp of fruits at low concentrations.